(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This reflection seeks to raise awareness of the importance of courtesy in social relations and is approached from a socioeducational perspective, with emphasis on the work of teachers, parents and representatives. Therefore, it is in the interest of teachers and parents to positively value behavior based on good manners and respect. This essay, the product of documentary research, draws on elements of grammar and pragmatics to compare ideas from renowned authors such as Alvarez Muro (2014), Grice (1998), Haverkate (1994), Fraser (1990) and Rosenblat (2017). A sociolinguistic awareness of politeness in the educational context can enable people with good manners and manners, verbal and nonverbal, to achieve goals more effectively.